Penerapan Metode K-Nearest Neighbor pada Aplikasi E-Kuliner untuk Strategi Marketing Wisata Kuliner Indonesia - Siti Asmiatun; Vensy Vydia; Edi Widodo (Universitas Multimedia Nusantara, 2020)
In recent years, the progress of the culinary business in the city of Semarang has increased. This is marked by the emergence of a lot of business creativity that follows consumer tastes. This creativity can be seen from the variety of culinary product variants sold by culinary entrepreneurs. From the research that has been done, there is still no research that filters and gives grade on food or drink in order to provide prices that are in accordance with the quality of food or drinks. Therefore to address the needs of culinary entrepreneurs, it takes an application of Culinary E-Business that can be a bridge for culinary entrepreneurs in the city of Semarang to receive orders online. It is expected that this application can determine food quality standards that will be marketed through this e-business application by providing grade A, B, and C. labels To determine food grade, this study uses the K-Nearest Neighbor method. By determining the price standards for similar foods, so there is no price competition for similar foods that can lead to the death of food entrepreneurs with small capital. So that it can move the people's economy by providing the means to expand the regional food marketing network, so that food entrepreneurs have a greater chance to develop.